Decisive Effects of Life Stage on the Gut Microbiota Discrepancy Between Two Wild Populations of Hibernating Asiatic Toads (Bufo gargarizans) - Song, Xiaowei; Zhang, Jingwei; Song, Jinghan; Zhai, Yuanyuan (Frontiers in Microbiology, 2021)
Until now, effects of driving factors on the gut microbiota of amphibians are still mostly confounded. Due to a long-term fasting, hibernating amphibians are ideal experimental materials to explore this question. In this study, we characterized small intestine microbiota of adult hibernating Asiatic toads (Bufo gargarizans) collected from two geographical populations using 16S rRNA amplicon sequencing technique, and evaluated the effects of non-dietary factors (i.e., sex, life stage, health condition and genetic background). The most dominant phylum in the gut of hibernating Asiatic toads was Proteobacteria, among which five core OTUs existed in all samples. We detected a greater discrepancy of gut microbiota between geographical populations than sexes. In addition to the sex, host genetic background showed a minor effect on the gut microbiota variation. Furthermore, life stage was determined to be the decisive factor driving the gut microbiota discrepancy between populations. However, a large proportion of the gut microbiota variation (~70%) could not be explained by the measured deterministic factors. Therefore, other factors and/or stochastic processes may also play key roles in shaping gut bacterial community of hibernating amphibians.